EFFECT OF FINANCIAL PERFORMANCE ON COMPANY VALUE AT PT. GUDANG GARAM Tbk - nurmi yanti; Nafisah Nurulrahmatiah (Universitas Muhammadiyah Makassar, 2021)
This study was conducted to determine the effect of financial performance as measured by liquidity and solvency ratios on firm value at PT. Gudang Garam tbk in the period 2012-2018. The data used in this study are the financial statements of PT. Gudang Garam tbk from 2012-2018. The population used in this study is financial statement data for 29 years, from 1990 to 2018 with the sample used in the form of balance sheet and profit and loss statements for 7 years from 2012 to 2018. The sampling technique uses purposive sampling with data criteria in the latest publications and data. The method of analysis in this research is the method of associative statistical analysis. The data collection technique used literature study and documentation methods while the data analysis used was multiple linear regression, classical assumption test, correlation coefficient, multiple determination coefficient and hypothesis test (2-party t test) using the SPSS software program. From this study it can be concluded that the liquidity ratio has no significant effect on firm value, while the solvency ratio has no and significant effect on firm value. And simultaneous research (f test) shows that there is a significant influence between the liquidity and solvency ratios on firm value